Effects of Fish Oil and Tomato Powder Supplementation in Mojosari Ducks Diet on Egg Quality - Andri, Faizal; Widodo, Eko; Djunaidi, Irfan Hadji (Graduate School, Universitas Brawijaya, 2017)
This research aimed to examine the effects of fish oil and tomato powder supplementation on egg quality of Mojosari ducks. A total of one hundred and forty Mojosari ducks (consisted of 20 male and 120 female ducks), aged at 40 weeks old, were randomly allotted into 20 flocks (each flock consisted of 1 male and 6 female ducks). Method used was experiment in a Completely Randomized Design with 5 treatments and 4 replications. Dietary treatments used were T0: basal diet (control), T1: basal diet + 1% FO, T2: basal diet + 2% FO, T3: basal diet + 1% FO + 1% TP; T4: basal diet + 2% FO + 1% TP. Data were analyzed using one-way analysis of variance (ANOVA). Result showed that supplementation of fish oil and tomato powder did not significantly affect (P>0.05) external egg quality (egg shape index, shell surface area, shell thickness and specific gravity). Dietary treatments also had no significant effect (P>0.05) on internal egg quality (albumen volume, yolk volume, albumen index, yolk index and Haugh unit). It is concluded that there was no detrimental effect of fish oil and tomato powder supplementation in Mojosari ducks diet on external and internal egg quality.Keywords: antioxidant, Haugh unit, laying duck, omega-3 fatty acids, poultry.